Implementing Digital Education Policy through e-Rapor in Rural Indonesian High Schools: A Case Study of SMAN 1 Abung Tinggi - Aghisna Amalia Putri; Intan Fitri Meutia; Dedy Hermawan; Bambang Utoyo S (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the implementation of Indonesia’s digital education policy through the e-Rapor system in a rural public high school, SMAN 1 Abung Tinggi, using a qualitative descriptive case study approach. Drawing on in-depth interviews, non-participant observations, and document analysis, the research analyzes e-Rapor as a socio-technical instrument embedded in organizational routines rather than as a standalone technological application. The findings show that e-Rapor improves administrative efficiency, data integration, and reporting accountability, while simultaneously reshaping assessment practices, professional roles, and internal coordination mechanisms. Implementation outcomes are strongly mediated by human resource capacity, leadership practices, infrastructural constraints, and informal adaptive arrangements developed at the school level. Digital literacy gaps and unstable connectivity remain persistent challenges, yet peer collaboration and managerial support enable functional policy adaptation. The study demonstrates that digital policy effectiveness in rural contexts emerges from institutional mediation and organizational learning, not from technological deployment alone. Theoretically, the research contributes to policy implementation and digital governance by highlighting adaptive compliance, while methodologically it demonstrates qualitative inquiry for capturing contextualized dynamics.